The Effect of Sharia Share, Corporate Sukuk and Sharia Mutual Fund on National Economic Growth 2013-2020 - Siti Rohayani; Hidajat Sofyan Widjaja; Reny Fitriana Kaban (MEC-J (Management and Economics Journal), 2022)
The Islamic capital market, which includes sharia shares, corporate sukuks and sharia mutual funds, has contributed significantly to the national economic growth. Previous studies have shown different results regarding this issue. Therefore, it is necessary to to obtain more up-to-date data result.The purpose of this study is to analyze the effect of Sharia share, corporate sukuk and Sharia mutual fund on national economic growth for the 2013-2020 period. The method used is a quantitative method with secondary data. The data for Sharia share, Corporate Sukuk and Sharia Mutual Funds were obtained from the financial quarterly reports of Financial Services Authority and the data for national economic growth from Gross Domestic Products quarterly reports of Central Statistics Bureau for the period 2013-2020. Based on the statistical tests, partially Sharia share and Sharia mutual fund have a negative and insignificant effect on national economic growth, while corporate sukuk have a positive and significant effect on national economic growth. Simultaneously all variables have a positive and significant impact on national economic growth. Based on the results of the R Square test, the magnitude of the influence of Sharia Share, Corporate Sukuk and Sharia Mutual Fund on National Economic Growth is 58%.Thisimplicates to the capital market issuer for improving their performance until the optimum level especially for the sharia shares and sharia mutual funds so their contribution to the national economic growth would be significantly effective.